Histoires et mémoires de deux centres de stockage de déchets nucléaires - Blanck, Julie; Patinaux, Leny (Socio-anthropologie, 2020)
This article draws a parallel between the history of two nuclear waste repositories in France: the first disposal facility in La Hague (Manche) in 1968, and the underground storage project for high-level nuclear waste whose construction has been postponed since the late 1980s. The history of these two projects shows different relationships to memory of the sites. When the Manche disposal facility was closed, the memory of this storage became a subject of controversy: the type of waste stored and memory technologies are from then the main topic of debate. Instead, the memory transmission of a nuclear waste storage designed to isolate radionuclides from nuclear power production during the next million years is fascinating. Nevertheless, it never became a main issue in nuclear waste governance debates in France. By contrast, the memories of struggle against nuclear waste burying mark this history.